Pengembangan Objek Wisata Kabupaten Mojokerto Dengan Pendekatan Collaborative Governance (Studi Kasus Pemandian Air Panas Pacet) - Yusuf Hariyoko; Ega Purnamasari Biadi; Adi Susiantoro (Governance, JKMP (Governance, Jurnal Kebijakan & Manajemen Publik), 2021)
Development of Hot Spring Tourism Object located in Pacet Mojokerto Regency is very beautiful with the original hotwater from Mount Welirang makes visitors come both inside and outside Mojokerto, not only served with hot springs butwith the beauty of the mountains fresh and cold can be felt by tourist visitors. The results showed that the Department ofYouth Tourism and Sports can see that (1) Transportation is in developing road ac cess to tourist attractions is good, there are already signs of directions are expected to add transportation agents travel agencies, (2) Service Facilities need improvement so that what is obtained by tourists is satisfied and feel happy. It can be conclu ded that the improvement of facilities must be considered again, (3) Information and Promotion can be concluded for the promotion that has been done well and developed among the media, (4) Institutional Design collaboration relationship that occurred betwe en the government based on the results of the interview above by researchers obtained institutional design that is between Disparpora, Coordinator of Tourism Object Management , Tourist Visitors, and surrounding communities and need to add a private role such as travel agency , and like the promotion of other events have been well implemented